The First Metal Complexes of 4, 6-diamino-1-hydro- 5-hydroxy-pyrimidine-2-thione: Preparation, Physical and Spectroscopic Studies, and Preliminary Antimicrobial Properties. (6th January 2009) - Mostafa, Sahar I.; Papatriantafyllopoulou, Constantina; Perlepes, Spyros P.; Hadjiliadis, Nick
Abstract : The new complexes[ M 2 O 5 L 2 ( H 2 O ) 2 ] ⋅ H 2 O ( M = Mo, 1 ; M = W, 2 ), [ RuL 2 ( H 2 O ) 2 ] ⋅ H 2 O (3), [ ML 3 ] ⋅ x H 2 O ( M = Rh, x = 2, 4 ; M = Ir, x = 1, 5 ), [ RhL 2 ( PPh 3 ) 2 ] ( ClO 4 ) ⋅ 2 H 2 O (6), [ PdL 2 ] ⋅ 2 H 2 O (7), [ PdL ( phen ) ] Cl ⋅ H 2 O (8), [ Re OL 2 ( PPh 3 ) ] Cl (9) and[ UO 2 L 2 ] (10) are reported, where LH is 4, 6-diamino-1-hydro-5-hydroxy-pyrimidine-2-thione. The complexes were characterized by elemental analyses, physical techniques (molar conductivity, room-temperature magnetic susceptibility), and spectroscopic (IR, Raman, UV/VIS/ligand field, NMR, mass) methods. The ligandL − is in its thione form and behaves as a bidentate chelate with the deprotonated (hydroxyl) oxygen and the nitrogen of one amino group as donor atoms. Oxobridged dinuclear(1, 2) and various mononuclear(3–10) structures are assigned for the complexes in the solid state. The metal ion coordination geometries are octahedral(1–6, 9, 10) or square planar(7, 8) . The free ligand LH and complexes1, 4, 7, and8 were assayed in vitro for antimicrobial activity against two bacterial and two fungal cultures.